Alignment model for trunk road network maintenance outsourcing - Orugbo, Ena E.; Alkali, Babakalli M.; Desilva, Anjali; Harrison, David K. (Journal of Civil Engineering and Management, 2016)
Road maintenance outsourcing is now the foremost strategy by which road authorities procure maintenance works. Despite growing application of road maintenance outsourcing, there are conflicting estimates on the effectiveness of road maintenance outsourcing and shortage of appropriate models to align over optimistic expectations of road authorities from road maintenance outsourcing with substantiated benefits. This paper investigates the efficacy of road maintenance outsourcing. In this paper, the different variants of road maintenance outsourcing and road maintenance works are evaluated with a SWOT analysis and a comprehensive literature review respectively. In addition, a road maintenance outsourcing alignment model based on a decision tree and Balance Score Card is proposed and illustrated with a Nigerian trunk road network authority as a case study. The result of the SWOT analysis and comprehensive literature review establishes fresh insight into road maintenance outsourcing dynamics. The presented road maintenance outsourcing alignment model provides adequate pathways that could assist road authorities identify the most appropriate road maintenance outsourcing variant for road maintenance procurement. In addition it aligns actual benefits and expectations of road maintenance outsourcing and facilitates development of SMART metrics for effective assessment of road maintenance outsourcing. The proposed model is applicable across other infrastructures. First published online: 01 Sep 2015